2021
DOI: 10.1007/s11356-020-11845-2
|View full text |Cite
|
Sign up to set email alerts
|

Technological innovation, financialization, and ecological footprint: evidence from BEM economies

Abstract: Despite the growing interest in researches on the impact of technological development on the carbon emissions, the effect of technological innovation on the other indicators of environmental degradation is of little interest. In order to close this gap, the aim of this study is to determine the effects of technological innovation on both carbon emission and ecological footprint for big emerging markets (BEM) countries. In doing so, the environmental impacts of the financialization process are also explored, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(44 citation statements)
references
References 80 publications
7
37
0
Order By: Relevance
“…In addition, [ 13 ] tested the effect of technological innovation on Pakistan’s ecological footprint over the period between 1992 and 2018 and established that technological innovation contributes to the ecological footprint. Destek and Manga [ 22 ] studied the effect of technological innovation on ecological footprint and carbon emission in large emerging markets over the period between 1995 and 2016. They concluded that technological innovation reduces carbon emissions, whereas technological innovation does not impact the ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, [ 13 ] tested the effect of technological innovation on Pakistan’s ecological footprint over the period between 1992 and 2018 and established that technological innovation contributes to the ecological footprint. Destek and Manga [ 22 ] studied the effect of technological innovation on ecological footprint and carbon emission in large emerging markets over the period between 1995 and 2016. They concluded that technological innovation reduces carbon emissions, whereas technological innovation does not impact the ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thirdly, literature is scarce on the impact of environmental technologies and ecological footprint. The impact of technological development on the EF and carbon emission of big emerging countries from 1995 to 2016 using second-generation panel data techniques is examined (Destek and Manga 2021). Moreover, Hussain and Dogan (2021) checked the effect of environmental technologies on the ecological footprint in BRICS for the period 1992 to 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Erdogan ( 2021 ) for the BRICS nations and Guo et al ( 2021 ) for China discovered that technological advancements generate an enabling environment that decreases energy usage, increases energy efficiency, and finally leads to carbon emissions mitigation. These findings are further supported by Anser et al ( 2021b ) for EU countries; Yang et al ( 2021 ) for BRICS economies; Shan et al ( 2021 ) for Turkey; Baloch et al ( 2021 ) for OECD countries; Ahmad and Raza ( 2020 ) for America; An et al ( 2021 ) for Belt and Road host countries; Khan et al ( 2020 ) for G7 countries; Destek and Manga ( 2021 ) for big emerging market; and Udeagha and Ngepah ( 2020 ) for South Africa. However, our findings contrast those of Dauda et al ( 2021 ), who concluded that technological progress in Sub-Saharan African nations degrades environmental quality.…”
Section: Empirical Results and Their Discussionmentioning
confidence: 52%